2022
DOI: 10.1038/s41598-022-06993-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Analgesia Nociception Index (ANI) and self-reported measures for diagnosing pain in conscious individuals: a systematic review and meta-analysis

Abstract: The Analgesia Nociception Index (ANI), an objective measure of pain based on heart rate variability (HRV), has its usefulness in awake patients still unclear. This systematic review and meta-analysis aimed to assess ANI's accuracy compared to self-reported pain measures in conscious individuals undergoing medical procedures or painful stimuli. PubMed, Ovid, Web of Science, Scopus, Embase, and grey literature were searched until March 2021. Of the 832 identified citations, 16 studies complied with the eligibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Baroni et al conducted a meta-analysis to assess ANI's potential in awake patients after surgery [18]. Of the 16 diverse articles, 9 studies focusing on NRS and ANI were included for meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Baroni et al conducted a meta-analysis to assess ANI's potential in awake patients after surgery [18]. Of the 16 diverse articles, 9 studies focusing on NRS and ANI were included for meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have suggested that ANI is an objective and reliable indicator for predicting intraoperative pain [ 10 , 20 , 27 ]. Although its correlation has been weak when applied to conscious patients, a previous meta-analysis has reported the ANI to be more helpful when applied immediately after sedation or surgery [ 28 ]. To date, there is insufficient evidence to assess nociception or pain solely using ANI, especially in the awake state.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have reported that ANI values in patients differ when under general anesthesia and when in a conscious state [ 56 ]; thus, ANI in an awake state is difficult to interpret [ 57 ]. Baroni et al performed a meta-analysis of nine studies that assessed ANI and self-reported measures in conscious patients [ 58 ]. They found a weak negative correlation between ANI and NRS in the post-anesthetic recovery room ( r = −0.0984; 95% CI −0.397 to 0.220, I 2 = 95.82%).…”
Section: Limitations Of Animentioning
confidence: 99%